SizweNtsalubaGobodo : managing the merger minefield (epilogue) - Ndaba, Zanele (SAGE Business cases., 2020)
Sekese explained that he and Gobodo built the new culture by holding workshops, which began by acknowledging the differences between the two firms. "We then had to profile the personality of SNG as if she were a person, examine her ambitions, and from there we extracted behavioural traits of people, and particularly of the leaders, to determine how they should behave, what competencies a typical SNG leader should have, and we established what the minimum criteria were which would be used to evaluate our leaders," he said. "I have never done so many psychometric tests to find out my own competencies and weaknesses. I was humbled and got an executive coach for the first time. Throughout my career I never had a proper mentor - on the contrary, people almost destroyed my career when I was viewed as useless because of the colour of my skin."